PS-027 Availability of drug samples in outpatient clinics: opportunities and risks. (25th February 2017) - Darbon, F; Jaatoul, M; Atkinson, S; Bussières, JF
Abstract : Background: The Food and Drugs Act (FDA) does not allow direct consumer advertising for prescription drugs. At the hospital, distribution of drug samples is prohibited for hospitalised patients but is tolerated for outpatient clinics. Distribution of drug sample by physicians may compromise the optimal drug use process in hospitals and the community. Purpose: The objective of this study was to estimate the number of drug samples available in outpatient clinics in a teaching hospital in 2016 and to compare these numbers with 2007, 2009 and 2012. Material and methods: This was a cross sectional observational study conducted in a 500 bed teaching hospital. The inventory was conducted by 2 research assistants during 2 weeks each year through unannounced visits. The total number of units (dispensed format/drug) and doses of drug samples were calculated in 2007, 2009, 2012 and 2016. We calculated a ratio of units of drug samples per patient visits to estimate the potential patient exposure. Results: A total of 78 941, 74 972, 91 000 and 93 881 doses were found, respectively, in 2007, 2009, 2012 and 2016. Drug samples were found in 11 locations in 2016 out of 15 storage areas. The ratio of per patient visit was, respectively, 0.40, 0.38, 0.41 and 0.40. A total of 75% of doses (70 264/93 881) were not listed on the hospital drug formulary and 6% (5298/93881) had expired. Conclusion: The ratio of doses of drug samples per patient visit has remained stable over the past 10 years; however, the total number of doses of drug samples reached a peak in 2016 with 93 881 doses. While we believe the majority of drug samples do not contribute to optimal drug use, it is difficult to proscribe their presence in a large healthcare facility where numerous prescribers and pharmaceutical representatives walk in. Drug samples are quite prevalent in hospitals. Pharmacists and all stakeholders should be aware of their presence when they treat a patient and complete medication reconciliation. No conflict of interest